2011
DOI: 10.1007/s00428-011-1144-4
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis in triple-negative adenoid cystic carcinomas of the breast

Abstract: We compared microvascular density (MVD), lymph vessel density (LVD), and the expression of hypoxia pathway-associated proteins between primary triple-negative adenoid cystic carcinoma of the breast (TN-ACC) and grade-matched triple-negative breast carcinomas of no special type (TNBC). Twelve TN-ACC and 15 TNBC were investigated immunohistochemically for CD31, podoplanin (D2-40), von Hippel-Lindau protein (pVHL), and hypoxia-inducible factor-1alpha (HIF-1α) protein. All cases were lymph node negative (pN0). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Our results showed that the f values were higher in TNBC compared to HER2-type cancers. This correlates with the research results of Vranic [32]; they thought TNBC exhibited increased f compared with other subtypes, which suggests that this type of cancer undergoes increased tumor angiogenesis. This is the exact reason for the increase in APT values.…”
Section: Discussionsupporting
confidence: 89%
“…Our results showed that the f values were higher in TNBC compared to HER2-type cancers. This correlates with the research results of Vranic [32]; they thought TNBC exhibited increased f compared with other subtypes, which suggests that this type of cancer undergoes increased tumor angiogenesis. This is the exact reason for the increase in APT values.…”
Section: Discussionsupporting
confidence: 89%
“…TNBC samples exhibited increased fast ADC and fraction of fast ADC values compared with other subtypes, which suggests that this type cancer undergoes increased tumor angiogenesis. It has been reported that TNBC also exhibited increased MVD compared with other subtypes of cancer ( 52 ). The tumor edge tissues from TNBC samples exhibited increased fraction of fast ADC values compared with other tissue types, including TNBC tumor tissue which may be associated with increased blood supply to the tumor and the internal necrosis of the tumor.…”
Section: Discussionmentioning
confidence: 97%
“…Our group has recently reported on two breast AdCCs with high-grade transformation; our findings confirmed that progression occurred via the acquisition of additional genetic events and/or clonal selection; however, none of the genetic alterations reported in the progression of salivary gland AdCCs were found in breast AdCCs. 7 In a distinct study of a single breast AdCC metastasizing to the kidney, 92 PIK3CA and PTEN mutations were found in both the primary and metastatic tumors, but, the metastatic deposits showed increased PTEN promoter methylation and lower PTEN gene expression levels. It seems therefore unlikely that a single genetic event is responsible for the high-grade transformation observed in human AdCCs.…”
Section: Tnbcs: the Importance Of Histologic Subtypingmentioning
confidence: 99%